Expectant, medical, or surgical management of first-trimester miscarriage: a meta-analysis - Sotiriadis, Alexandros; Makrydimas, George V.; Papatheodorou, Stefania; Ioannidis, John P. A. (My University, 2005)
Objective: To quantify the relative benefits and harms of different management options for first-trimester miscarriage. Data Sources: Medline, Embase, and Cochrane Controlled Trials Register searches (1966 to July 2004), including references of retrieved articles. Methods Of Study Selection: Randomized trials assigning women with first-trimester missed or incomplete miscarriage to surgical, medical, or expectant management were included. Primary outcomes were successful treatment and patient satisfaction. Secondary outcomes included moderate or severe bleeding, blood transfusion, emergency curettage, pelvic inflammatory disease, nausea, vomiting, and diarrhea. Comparisons used the risk difference. Between-study heterogeneity and random effects summary estimates were calculated. Tabulation, Intagration, And Results: Complete evacuation of the uterus was significantly more common with surgical than medical management (risk difference 32.8%, number needed to treat 3, success rate of medical management 62%) and with medical than expectant management (risk difference 49.7%, number needed to treat 2). Success rate with expectant management was spuriously low (39%) in the latter comparison. Analysis of cases with incomplete miscarriage only showed that medical management still had two thirds the chance to induce complete evacuation compared with surgical management, but it was better than expectant management. Data from studies that evaluated outcome at 48 hours or more after allocation indicated again that medical management had a better success rate than expectant management but a worse success rate than surgical management; expectant management probably had much lower success rates than surgical evacuation, but data were very sparse. Patient satisfaction data were sparse. Moderate or severe bleeding was less common with medical than expectant management (risk difference 3.2%) and possibly surgical management (risk difference 2.1%). There was a considerable amount of missing information, in particular for secondary outcomes. Conclusion: One additional success can be achieved among 3 women treated surgically rather than medically. Expectant management has had remarkably variable success rates across these studies, depending probably on the type of miscarriage. Greater standardization of outcomes should be a goal of future research.
Keywords: Methotrexate; Mifepristone; Misoprostol; Prostaglandin; Prostaglandin E2; Pregnancy; Pregnancy trimester; First trimester pregnancy